Synthesis and characterization of zinc-tin-mixed oxides thin films. (November 2018) - Dabbabi, Samar; Nasr, Tarek Ben; Ammar, Souad; Kamoun, Najoua
Abstract: The mixed oxides thin films were prepared by spray pyrolysis method on glass substrates using different molar ratios of zinc and tin in the starting solution Zn/(Zn + Sn) = 25 at.%, 50 at.%, and 60 at.%. The structural, morphological and optical properties were characterized by X-ray diffraction (XRD), atomic force microscopy (AFM), Scanning Electron Microscopy (SEM) and spectrophotometry. XRD analysis indicate the coexistence of both the hexagonal phase of ZnO and the tetragonal phase of SnO2 for all mixed thin films. Microstructural parameters such as micro-strain and crystallite size suggest the good crystallinity of mixed thin film at 60 at.%. Optical analysis by means of transmittance T ( λ ) and reflectance R ( λ ) measurements allowed us to determine the optical constants for single and mixed oxides. The refractive index dispersion was adequately described by the Wemple-Di-Domenico model. The values of oscillator energy E0, dispersion energy Ed, high-frequency dielectric constant ε ∞ as well as the ratio of the carrier concentration to the effective mass N/m ∗ were estimated according to both Wemple-Di-Domenico and Spitzer–Fan models. Highlights: Preparing mixed oxides (ZnO, SnO2 ) thin films by spray pyrolysis on glass substrates. Film deposited at 60 at.% has a larger crystallite size and a less microstrain, indicative the improvement of the crystallinity of the layer. Two different gap values are obtained for both mixed thin films at 50 and 60 at.% atomic ratios.